2021
DOI: 10.3390/nu14010126
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Energy-Rich Diet Increases Prefrontal BDNF in Sprague-Dawley Rats

Abstract: Findings of the effect of high-fat feeding including “Cafeteria Diets” (CAF) on brain-derived neurotrophic factor (BDNF) in the hippocampus (HIP) and prefrontal cortex (PFC) in rodents are conflicting. CAF is a non-standardized, highly palatable energy-rich diet composed by everyday food items for human consumption and is known to induce metabolic syndrome and obesity in rats. However, the highly palatable nature of CAF may counteract a negative effect of chronic stress on anticipatory behavior and synaptic pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…Since the c-Fos-IR cell levels of CTR-CAF rats were also not significantly different from CTR-chow rats in the PFC, we conclude that the PrL and IL of the PFC are not involved in this aspect of reward processing. This is in line with another study that also failed to detect changes in monoamine neurotransmitters in the PFC after CAF exposure [52].…”
Section: Discussionsupporting
confidence: 92%
“…Since the c-Fos-IR cell levels of CTR-CAF rats were also not significantly different from CTR-chow rats in the PFC, we conclude that the PrL and IL of the PFC are not involved in this aspect of reward processing. This is in line with another study that also failed to detect changes in monoamine neurotransmitters in the PFC after CAF exposure [52].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the effects of an HFD on BDNF, the literature reports both increases and decreases in BDNF levels in the prefrontal cortex. For example, Virtuoso et al reported that a chronic cafeteria diet on a restricted schedule increases BDNF levels in the prefrontal cortex (PFC) of rats [38]. Nevertheless, Miao et al found that in pregnant female mice, HFD induced decreases in BDNF in the hippocampus and prefrontal cortex, but increases in the amygdala [39].…”
Section: Discussionmentioning
confidence: 99%
“…This model shows increased adiposity and hepatosteatosis, white fat, and more inflammation in the adipose tissue and liver [14,41]. A chronic CAF on a restricted schedule has also been shown to increase BDNF levels and its receptor TrkB in the prefrontal cortex of rats [139].…”
Section: Cafeteria Diet (Caf)mentioning
confidence: 90%